Efficacy of periodic acid–Schiff stain in the diagnosis of onychomycosis – A cross-sectional study - Mohamed Salahudeen; Anita Ramdas; Arthi Elumalai; Kandasamy Ravichandran; Sheela Kuruvila (Journal of Current Research in Scientific Medicine, 2022)
Background: Onychomycosis is the fungal infection of the nail which needs to be differentiated from other causes of dystrophic nails due to its long-term treatment. Direct microscopic examination with potassium hydroxide (KOH) mount along with fungal culture shows inconsistent sensitivity. Thus, there is a need of more accurate and efficient method to detect onychomycosis. Aims and Objectives: This study aims to compare periodic acid–Schiff (PAS) stain with KOH and nail fungal culture in the diagnosis of onychomycosis. Materials and Methods: This was a cross-sectional study conducted in the dermatology outpatient department of a tertiary care center in South India from July 2019 to July 2021. A total of 93 patients with clinical suspicion of onychomycosis were included in the study and evaluated for the following three methods: KOH mount, nail fungal culture, and PAS stain. Results: Of the 93 patients, PAS was positive in 82 (88%) cases, KOH mount was positive in 32 (34%) cases, and nail fungal culture showed positive results in 49 (53.2%) patients. The percentage of positivity of combined PAS and culture was 89 (95.7%) and combined KOH and culture was 63 (65.7%). The culture yielded growth in 49 patients showing dermatophytes in 2, yeasts in 35, and nondermatophyte molds (NDMs) in 12 specimens The most common isolated species was Candida tropicalis found in 11 (22.4%) followed by Candida species in 8 (16.3%), Candida albicans in 7 (14.2%), and Trichosporon species in 6 (12.2%) specimens. Among the NDMs, Fusarium oxysporum was the most isolated found in 5 (10.2%). Conclusion: The importance of this study is to highlight the utility of PAS stain in the diagnosis of onychomycosis which otherwise may be missed with KOH and culture. PAS can be performed as an additional test to KOH mount and nail fungal culture to close the diagnostic gap.